Off-Pump Coronary Artery Bypass Grafting in Acute Coronary Syndrome: Focus on Safety and Completeness of Revascularization - Neumann, Anneke; Vöhringer, Luise; Fischer, Julia; Mustafi, Migdat; Schneider, Wilke; Krüger, Tobias; Schlensak, Christian (The Thoracic and Cardiovascular Surgeon, 2019)
Background Emergency coronary artery bypass grafting (CABG) in the setting of acute coronary syndrome (ACS) has been associated with increased morbidity and mortality. Avoiding cardiopulmonary bypass might be advantageous, but the role of off-pump CABG (OPCAB) remains controversial, as it has been associated with incomplete revascularization in several studies. The objective of this study was to evaluate the feasibility, efficacy, and outcome of OPCAB surgery in ACS patients.Methods We performed a retrospective review of ACS patients who underwent on-pump CABG (ONCAB) or OPCAB, either emergently or delayed, at our institution.Results Between January 2015 and December 2016, a total of 205 consecutive ACS patients underwent either ONCAB (109 patients, 53.2%) or OPCAB surgery (96 patients, 46.8%). EuroSCORE II levels (5.6 ± 7.2 vs 4.9 ± 6.5, p = 0.226) and demography were comparable between groups.A trend towards lower postoperative mortality was observed in OPCAB patients (2.1 vs 5.5%). The incidence of postoperative stroke and low cardiac output syndrome, as well as the duration of inotropic support and the need for re-sternotomy, was significantly lower in the OPCAB group (p < 0.05).CABG performed instantly in an emergency situation was not associated with increased mortality or morbidity when compared with delayed procedures, and OPCAB surgery in emergency patients was associated with lower postoperative morbidity and shorter stays in the intensive care unit (p < 0.05).There were no differences in completeness of revascularization between groups (median 1 [1–1.33;0.33–1.67] OPCAB versus median 1 (1–1.33;0.67–2) ONCAB, p = 0.617), even in the emergency setting.Conclusion OPCAB surgery is safe and effective in ACS and may be considered in hemodynamically stable patients in the emergency setting.
Keywords: coronary artery bypass grafting; off-pump coronary artery bypass grafting; acute coronary syndrome; myocardial infarction